Pengaruh Pengetahuan Akuntansi dan Soft Skill Berbasis Teknologi Terhadap Produktivitas Industri Manufaktur - Dwi Hapsari, Norma (Universitas Sains dan Teknologi Komputer, 2024)
The development of information technology in the era of Industry 4.0 and Society 5.0 necessitates accounting professionals to enhance their AI-based information technology knowledge supported by soft skills. This research utilizes primary data through questionnaire-based data collection. The study's population comprises employees of Lifetime Design Manufacture using Accurate software, with purposive sampling as the sampling technique. The research findings indicate that accounting knowledge, information technology knowledge, and soft skills significantly impact employee performance. The study has limitations that require refinement and development. Future research could identify additional variables influencing employee performance for a more comprehensive corporate strategy.